From the house of pau a pique and the setting of the clay: the experience of the "Rights in Motion" university extension project in the quilombola Mundo Novo community - Buíque/PE (Revista Internacional de Folkcomunicação, 2020)
This article aims at illustrating the importance of the links between research and extension projects from the experience developed in the Mundo Novo community, located in the district of Buíque, state of Pernambuco, Brazil, which was a starting point for the "Rights in Motion" project. Its general objective is to observe how studies about Mundo Novo have collaborated towards actions that have gone beyond university walls and promoted a significant transformation in the community.  Specific goals aim at showcasing the importance of regulating the remaining quilombo communities, as well as introducing the collaboration of the "Rights in Motion" extension project in the Mundo Novo community. The hypothetico-deductive method was used for this purpose. The project has obtained results, as it was possible to follow and develop actions to strengthen the quilombola identity during the twelve months.   Rights in motion; Mundo Novo Community; Quilombo; Culture.